Implementasi Strategi Digital Marketing Terintegrasi dalam Upaya Peningkatan Penjualan Usaha Kopi "Kangmas Coffee" di Dusun Kebonlegi Kabupaten Semarang - Arista Candra Irawati; Ari Siswanti; Hani Irhamdessetya; Dewi Purwanti; Purwati Purwati (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Coffee is the third most consumed beverage in the world after water and tea. Indonesia, being a tropical country, is the fourth largest coffee producer globally. In Semarang Regency, Central Java, there is a home-based coffee business called "Kangmas Coffee," founded by Martina Rinarsih in 2017. The business produces three premium coffee variants: Arabica, Robusta, and Liberica, processed using both dry and wet methods. Kangmas Coffee products are marketed to various regions through digital platforms and even won the prestigious 13th Indonesian Specialty Coffee Contest (KKSI) in 2021. Despite its success in specialty coffee, local marketing efforts remain limited due to insufficient promotion and intense competition from other coffee businesses. This is a common challenge faced by small businesses in Indonesia. In the current digital age, the potential of digital marketing offers a viable solution to these problems. By leveraging digital marketing, businesses like Kangmas Coffee can increase their visibility, reach wider audiences, and ultimately boost sales. Effective digital marketing strategies such as search engine optimization (SEO), social media engagement, and online advertisements can create new economic opportunities and help home-based coffee businesses expand their customer base. This is particularly crucial for small and medium enterprises (SMEs) operating in a competitive market. This community service activity focused on empowering local coffee entrepreneurs with digital marketing skills. It was conducted in a participatory manner, involving pre-tests, socialization sessions, interactive discussions, and post-tests. The results showed a significant increase in participants’ understanding of digital marketing, with a 53% improvement in their knowledge. This newly acquired knowledge can be instrumental for businesses like Kangmas Coffee, helping them enhance their competitiveness and sustainability in the local market. By embracing digital marketing, Kangmas Coffee and similar enterprises can thrive and contribute to the local economy